Persepsi Masyarakat Terhadap Human Elephant Conflict (HEC) dan Eksistensi Gajah Sumatera di CRU Sampoiniet Kabupaten Aceh Jaya, Provinsi Aceh, Indonesia - Najmi Rinjani Ferdian; Fathiya Rahma; Abdurrahman Hanif; Muhammad Ghazy Bhaltazar; Cut Nurul Azizah; Maria Ulfa; Abdullah Abdullah; Yuri Gagarin; Zulfikar Zulfikar; Ikhlas Wahid (Jurnal Penelitian Pendidikan IPA, 2023)
The increase in the human population has an impact on the expansion of the agricultural and plantation sectors. This causes a decrease in the amount of forest area which results in conflicts between humans and elephants. The purpose of the study was to determine the people's perception of the Sumatran elephant conflict and to determine the existence of male Sumatran elephants. The research was conducted in August 2022 at CRU Sampoiniet, Ie Jeureungeh village, Aceh Jaya district, Aceh province. The research method is descriptive qualitative and focal animal sampling. Data was collected by means of interviews, observation, and documentation. The results of the study revealed that the conflict between wild elephants had decreased since the existence of the CRU Sampoiniet who helped overcome the wild elephant conflict in the village area of ​​Ie Jeureungeh, however, currently there are still some minor disturbances and have an impact on the surrounding community. Some people want the environment around their plantations to be bordered by elephants through electric fences. Based on the results of observations, there are two types of feed provided by the manager and consumed by the tame elephants, namely sensitive plant (Mimosa pudica), cogon grass (Imperata cylindrica).